Apakah Pajak Masih Menjadi Determinan Utama? Peran Corporate Governance dan Mekanisme Bonus dalam Keputusan Transfer Pricing di Indonesia - Imelda De Lavega; Willy Nofranita (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
Transfer pricing has become a critical issue in international taxation as it is often associated with profit shifting and tax avoidance strategies. This study aims to examine the effect of tax, corporate governance, and bonus mechanisms on transfer pricing decisions in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2021–2024. The study employs a quantitative approach with an associative research design and applies multiple linear regression analysis to 60 observations selected through purposive sampling. The findings reveal that tax and bonus mechanisms do not significantly affect transfer pricing decisions, suggesting that economic incentives are not always the primary drivers of related-party transaction policies. In contrast, corporate governance, proxied by institutional ownership, has a significant effect, highlighting the crucial role of monitoring mechanisms in limiting managerial opportunism. Simultaneously, all variables significantly influence transfer pricing decisions. These results emphasize that transfer pricing practices are more strongly driven by corporate governance mechanisms than by purely economic factors, underscoring the importance of good corporate governance in enhancing transparency and accountability in corporate decision-making.